Measuring the Effects of an On-Line Training Module for School Psychologists Working with Traumatized Children: A Pilot Study - (:unkn) unknown (My University, 2012)
The present study was designed to address the current lack of trauma training provided to school psychologists. Specifically, this study employed a randomized, controlled design to test the efficacy of an on-line training targeting school psychology graduate student trainees' awareness of the signs and symptoms of child abuse as well as their knowledge of mandated reporting responsibilities. Results indicated that school psychologist trainees who completed the on-line training module reported greater awareness of the signs and symptoms of child abuse after viewing the module than did those school psychologist trainees who did not view the module. Similarly, school psychologist trainees who completed the on-line training module reported greater awareness of the signs and symptoms of child abuse after completing the on-line training than they did prior to completion. Moreover, this increased awareness of the signs and symptoms of child abuse among treatment participants was maintained three months post-training completion. No significant changes in knowledge of mandated reporting procedures were reported. Overall, these results suggest that an on-line training module focusing on child trauma may therefore be an effective way to increase school psychologist trainees' awareness of the signs and symptoms of child abuse, and, ideally, will improve the likelihood that they will recognize child abuse in practice.